(untitled) (Bangladesh Journal of Plant Taxonomy, 2020)
Living specimens of three colour forms (pink, white and yellowish white) of Nelumbo nucifera Gaertn. were observed in different natural habitats of Bangladesh and collected. Fresh specimens were studied in the field as well as in the laboratory. After detailed study it was concluded that the three colour forms available in Bangladesh belong to the same species, Nelumbo nucifera Gaertn. However, the yellowish white colour form, having many stamens petaloid, is considered as a new cultivar Nelumbo nucifera ‘Gomoti’ and reported here as the first lotus cultivar from Bangladesh. Bangladesh J. Plant Taxon. 27(2): 225-231, 2020 (December)